(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Euphemia is a complex universal communicative phenomenon, in its structure being a diverse linguistic phenomenon that plays an important role in the history of the development of society. Euphemisms are "a reflection of moral and spiritual culture, value attitudes,peculiarities of thinking and worldview of an individual and an ethnocultural community